Design of anonymous authentication protocol for RFID - DENG Miao-lei; MA Jian-feng; ZHOU Li-hua (Tongxin xuebao)
Safety requirements for RFID protocols were analyzed,and a low cost anonymous authentication protocol for RFID was proposed based on the universally composable security mode.The protocol was proven secure in the standard model.The new protocol provides anonymity,mutual authentication and concurrent security,and its implementation is feasible for a wide range of RFID architectures.